PLASTIC WASTE CONVERSION METHOD OF PLASTIC BOTTLE THROUGH TOGA CULTIVATION WITH ECO-FRIENDLY VERTICULTURAL SYSTEM - Agung Kurniawan (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2017)
The use of plastic and articles made of plastic has been increasing day by day. Enhancing the use of plastics is a consequence of technological, industrial and population development. One of alternative to handling plastic waste that is currently widely researched and developed is to recycle. Through environmental education on the community by converting plastic waste in the form of used plastic bottles into a planting medium in the eco-friendly vertical culture system cultivation. The method used in this research is classroom action research stage. The results of this study indicate significant progress in the first cycle which only utilizes used plastic bottles as vertebrate family medicinal plants (toga) planting medium and the second cycle shows the high public interest in the utilization of used plastic bottles with widespread planting location, maintenance system and the utilization of the cultivation result of family medicinal plants (toga)